Learning and Teaching of English in the Multilingual Classroom English Teachers' Perspectives, Practices, and Purposes - Krulatz, Anna; Neokleous, Georgios; Lorenz, Eliane (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue examines English teachers' perspectives on multilingualism and teaching English in multilingual contexts, implemented or planned teaching practices, and the teachers' intended goals. The research presented in this collection focuses on the perspectives of pre- and in-service teachers in a range of educational settings. Overall, the findings suggest that teachers continue to experience tensions between monolingual and multilingual ideologies and need continued support in adapting to the ever-evolving teaching contexts. While researchers and philosophers of language have been calling for a multilingual shift in education, teacher education and professional development programs lag behind in revising their curricula. Therefore, due consideration must be paid to the teachers; they are the agents of change, but they are also experts and professionals, and their views, knowledge, and pedagogical aims must be treated with respect. Many of the articles presented in this reprint illustrate that collaboration and mentorship between school and university partners can be fruitful, creative, and rewarding. The collection is a call for more opportunities for teachers and researchers to work in tandem to implement multilingual pedagogies that foster equal educational opportunities for all learners across different ages and stages of language development.